Ethos realization probe among ASNAF entrepreneurs in Selangor - Ashaari Sukar, Muhamad; Khusairi Tuan Azam, Syed; Iqbal Mohamed Azhari, Muhammad; Safeei, Roshidah; Sobre Ismail, Mohd; Mad, Salina; Suria, Khadijah (International Journal of Engineering and Technology, 2018)
Selangor Zakat Board (SZB) has been recognised as being the benchmark for other zakat institutions in Malaysia. One of the assistance programmes that is believed to be highly potential in resolving poverty issues among muslims is the Asnaf Economic Development Programme (AEDP), which is in the form of business capital assistance provision. The aim of this study is to investigate the relationship between the ethos that would affect the asnaf entrepreneursâ€™ physical performance via questionnaires. Out of 116 participants of the programme, only 59 responded for data collection purpose. The concluding results have shown that the variables of experience, knowledge and skills, and personal attributes have been identified in signifying a significant positive impact upon the performance of the participants of the programme.Â Â